International Treaty in the System of the Sources of the Constitutional Law - Tusupova, Zh.; Rahimbaeva, R.M. (Journal of actual problems of jurisprudence, 2018)
With the adoption of the Constitution of the Republic of Kazakhstan as of 1995 the significance of the interplay of National Law including Constitutional and International Law has increased. There appeared the necessity to bring the provisions of national law in conformity with the general recognized principles and norms of International Law, international treaties of the RK, as well as further taking into consideration of the indicated international regulators in the law enforcement activities. Researches of issues of a general theoretical nature pertaining to define the status of international treaties in the Republic of Kazakhstan, in its legal system are relevant up to the present. The Constitution of the Republic of Kazakhstan strengthens the priority of the international treaties ratified by the states before national law. In this connection the present work deals with the legal nature of international treaties their place in the system of current national law including the system of sources of the Constitutional Law, correlation of International and National Law. Key words: Constitution, sources of the Constitutional Law, International treaty , National Law, Constitutional Law, International Law.